Testbed Evaluation of Distributed Radio Timing Alignment Over Ethernet Fronthaul Networks - Freire, Igor; Almeida, Igor; Medeiros, Eduardo; Berg, Miguel; Lu, Chenguang; Trojer, Elmar; Klautau, Aldebaro (IEEE access, 2020)
This work investigates a mechanism for alignment of the timing on which spatially distributed and cooperative radio units transmit in radio-frequency (RF) when served over a packet-based fronthaul. It analyzes the problem by considering the imperfect clock synchronization of the radio units and the packet delay variation that fronthaul packets are subject to. Following the analysis, this paper proposes an implementation architecture for distributed RF transmission timing alignment based on synchronized triggering among radio units and centralized processing units. Throughout this discussion, special attention is given to the scheme's impact on the overall achievable fronthaul latency. Subsequently, this work discusses both hardware and software aspects of a prototype that was developed based on field-programmable gate arrays (FPGAs). In the end, it presents results obtained on an Ethernet fronthaul testbed where the referred FPGA-based prototypes implement radio units that are synchronized using the IEEE 1588 precision time protocol or by pulse-per-second references. Results validate the functionality of the proposed architecture and illustrate various relevant choices concerning system parameters.